2019
DOI: 10.3390/cancers12010073
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rho-Associated Kinase Suppresses Medulloblastoma Growth

Abstract: Medulloblastoma is one of the most common malignant brain tumor types in children, with an overall survival of 70%. Mortality is associated with metastatic relapsed tumors. Rho-associated kinases (ROCKs), important for epithelial-mesenchymal transition (EMT) and proper nervous system development, have previously been identified as a promising drug target to inhibit cancer growth and metastatic spread. Here, we show that ROCKs are expressed in medulloblastoma, with higher ROCK2 mRNA expression in metastatic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Another study showed that the overexpression of ROCK 2 in colon carcinoma cells which were inoculated into immunocompromised mice altered the epithelial morphology and promoted tumor cell invasiveness into the surrounding tissues ( 154 ). Also, targeting ROCK 1 and ROCK 2 blocked medulloblastoma proliferation through the impairment of EMT, TGF-β, and TNFα via NFkβ signaling ( 87 ), which suggests that blockade of ROCK signaling could be a target to impair anoikis resistance and metastasis. Although the role of Rho GTPase in cancer was reviewed ( 150 , 155 ), future studies are required to understand how targeting Rho GTPase can lead to the development of novel therapeutic agents for anoikis-resistant and metastasizing tumor cells.…”
Section: Rho Gtpasementioning
confidence: 99%
“…Another study showed that the overexpression of ROCK 2 in colon carcinoma cells which were inoculated into immunocompromised mice altered the epithelial morphology and promoted tumor cell invasiveness into the surrounding tissues ( 154 ). Also, targeting ROCK 1 and ROCK 2 blocked medulloblastoma proliferation through the impairment of EMT, TGF-β, and TNFα via NFkβ signaling ( 87 ), which suggests that blockade of ROCK signaling could be a target to impair anoikis resistance and metastasis. Although the role of Rho GTPase in cancer was reviewed ( 150 , 155 ), future studies are required to understand how targeting Rho GTPase can lead to the development of novel therapeutic agents for anoikis-resistant and metastasizing tumor cells.…”
Section: Rho Gtpasementioning
confidence: 99%
“…High expression of ROCK is associated with poor prognosis in medulloblastoma [ 45 ] neuroblastoma [ 46 ], and vascular tumors [ 47 ]. In medulloblastoma including metastatic medulloblastoma, mRNA levels of ROCK , especially ROCK2 , were highly expressed, which was associated with the overall survival of patients.…”
Section: Targeting Rock For Cancer Treatmentmentioning
confidence: 99%
“… 16 ROCK signaling is also involved in various tumorigenic pathways. 17 Ripasudil, a ROCK inhibitor, has been clinically approved for treating glaucoma and ocular hypertension in the form of an eye drop solution. Based on the immune-stimulatory effects of ROCK inhibitors, including enhancing the phagocytic activity of APCs and their ability to processing tumor antigens, and immediate cross-priming of naïve T cells, 18 ripasudil can be repurposed as an antitumor compound.…”
Section: Introductionmentioning
confidence: 99%